2008
DOI: 10.1245/s10434-007-9772-2
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Longitudinal Study of Cosmetic Outcome in Immediate Latissimus Dorsi Breast Reconstruction and the Influence of Radiotherapy

Abstract: Radiotherapy may adversely affect the cosmetic outcome of latissimus dorsi breast reconstruction, particularly if an implant is used, but this is not universal. Patient assessment of their cosmetic outcome may, however, differ significantly from the clinician's view.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 37 publications
2
57
0
1
Order By: Relevance
“…Although the majority of local failures occurred within the first 5 years of treatment, distant failure may occur later, and the patients in our study remain at risk for both locoregional and distant failure. Similarly, severe CC may not develop until several years after treatment [63] and the short median follow-up time of our study may give a falsely reassuring picture concerning our concept. As well, cosmesis outcome is known to decrease with time, particularly when RT is used.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Although the majority of local failures occurred within the first 5 years of treatment, distant failure may occur later, and the patients in our study remain at risk for both locoregional and distant failure. Similarly, severe CC may not develop until several years after treatment [63] and the short median follow-up time of our study may give a falsely reassuring picture concerning our concept. As well, cosmesis outcome is known to decrease with time, particularly when RT is used.…”
Section: Discussionmentioning
confidence: 67%
“…Similarly, Clough et al [47] reported deterioration in the esthetic outcome following implant-based IBR in a series of patients in whom only 8% had RT: from 86% acceptable results at 2 years to 54% at 5 years. Last, Thomson et al [63] reported a prospective study of cosmetic outcome in immediate LD breast reconstruction with and without RT. The cosmetic outcome of all reconstructions deteriorated over time, with the non-irradiated reconstruction producing the best long-term esthetic outcome and the irradiated implant reconstructions faring worst.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a prospective study by Thomson that assessed 73 women post immediate implant-assisted LD or autologous LD reconstruction with or without radiotherapy, there was no difference between the groups in terms of overall cosmetic outcome as determined by the patients. When a panel of independent cosmetic assessors reviewed the photographic evidence at different intervals over a defined time period, they concluded that while radiotherapy had an adverse effect on aesthetic outcome (p=0.0002) this was more obvious in the implant-assisted LD group [12].…”
Section: Resultsmentioning
confidence: 99%
“…Immediate breast reconstruction without radiotherapy, offers enhanced aesthetic and safe oncological outcomes, is more cost-effective and provides a positive psychological effect [12][13][14][15][16]. Despite this, less than 20% of patients having a mastectomy have immediate breast reconstruction in the United States [2].…”
Section: Introductionmentioning
confidence: 99%